Aboveground inputs rather than belowground root drive SOC responses to long term N addition in alpine grassland ecosystems of Qinghai-Tibetan Plateau - Ran Zhang; Hao Shen; Shikui Dong; Qiang Yu; Juejie Yang; Ying Li; Yaoming Li; Jiannan Xiao; Shuai Li; Hui Zuo; Hang Shi; Fengcai He; et al. (Agriculture, Ecosystems & Environment, 2026)

A genetic clash of sister groups: first-ever intergeneric and interspecific mitogenome comparisons between two close gall midge genera (Cecidomyiidae: Cecidomyiinae: Cecidomyiini): the floral and veggie-versatile Contarinia and the mango-mad Procontarinia, with phylogenetic applications - Xiu-Fang Dong; Yi-Fan Zhang; Xu-Yuan Gao; Ning-Bo Ma; Yu Ji; Yan-Fei Li; Yi-Ran Mu; Zheng-Hao Yue; De-Wei Wei; Yong-Hao Yu; Hai-Li Qiao; Wen-Jun Bu; et al. (Arthropod-Plant Interactions, 2026)

Lactiplantibacillus plantarum 5.1 attenuates ovarian fibrosis by modulating the gut microbiota and ovarian metabolism in a rat model of letrozole-induced polycystic ovary syndrome (PCOS) - Qiu-Ping Huang; Li-Ying Huang; Gui-Lian Liao; Chun-Xiang Huang; Ke-Ying Wang; Jie-Jing Xu; Hao-Ran Sun; Tie-Min Jiang; Jia-Le Song (Food Bioscience, 2026)

Elucidating the molecular mechanism of pancreatic lipase inhibition by small molecules from Auricularia auricula-judae via integrated biophysical approaches - Xia Yin; Hui-Min Li; Jia-Yang Xu; Han Wu; Meng-Yue Dong; Ke-Ran Hao; Jin-Ming Gao (Food Bioscience, 2026)

Integrative analysis of DEHP exposure and prostate cancer: Mechanistic insights and predictive modeling - Wen-Cai Zheng; Wen-Tao Xu; Chao-Ran Chen; Fei Lin; Shao-Hao Chen; Xiao-Dong Li; Xiong-Lin Sun; Qing-Shui Zheng; Yong Wei; Xue-Yi Xue; Zhi-Bin Ke; Ning Xu (Environmental Pollution, 2026)

Low N Deposition Coupled With Climate Warming Promote Soil Asymbiotic N Fixation via Increasing Microbial Specialists in Alpine Grassland - Ke Zhang; Yaoming Li; Ran Zhang; Anna Du; Zuyan Ma; Hang Shi; Juejie Yang; Wenli Ding; Hao Shen; Richard D. Bardgett; Huaiying Yao; Shikui Dong (Global Change Biology, 2026)
Biological nitrogen fixation (BNF) is a vital process for introducing new N into natural ecosystems, and this process has been demonstrated to be suppressed by high N deposition. However, the net ecological effect and underlying mechanisms of BNF under chronic low‐level N deposition, characteristic of terrestrial ecosystems, remain highly uncertain. Given that climate warming is a key environmental change factor concurrent with N deposition, it is important to investigate whether climate warming can change BNF activity and alter the effects of N deposition on BNF. To fill these knowledge gaps, we implemented a decade‐long‐term manipulation experiment in an alpine grassland ecosystem with 5 treatments, that is, experimental warming (W), low‐level N deposition (N L ), high‐level N deposition (N H ), combination of climate warming and low‐level N deposition (WN L ) and the control (CK). BNF rate was measured by 15 N 2 isotope discrimination. We found that N L significantly stimulated BNF by 112%, contrasting sharply with the complete suppression under N H . Climate warming alone increased the BNF rate by 123%, while the WN L amplified this effect, stimulating BNF by 234%. Structural equation modeling revealed that WN L selectively favored specific diazotrophic groups ( Desulfovibrio ), whose proliferation directly drove the observed BNF shifts. In this N‐limited alpine grassland, low‐level chronic N deposition, especially when combined with warming, fundamentally shifts the diazotrophic community structure by driving a process of niche contraction. This selection process functionally enriches specialized diazotrophs, resulting in a dramatic, positive feedback that significantly promotes the overall biological nitrogen input. Our findings highlight the potential for increased N inputs under realistic future climate scenarios and provide a scientific basis for precision N management in alpine grasslands, both on the Qinghai‐Tibetan Plateau and worldwide.

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Effects of nitrogen deposition on temporal stability and resistance of the alpine steppe plant communities on the Qinghai-Tibetan Plateau - Ran Zhang; Hao Shen; Shikui Dong; Qiang Yu; Bing Zhang; Jiannan Xiao; Shuai Li; Hui Zuo; Hang Shi; Fengcai He; Ke Zhang; Yuhao Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Trichothecenes with cytotoxic activity and benzene derivatives with hypolipidemic activity from trichothecium sp - Liang Xing; Yi-Fan Guo; Ke-Ran Hao; Yi-Ting Wu; An-An Yang (Natural Product Research, 2025)

Triptolide exposure triggers ovarian inflammation by activating cGAS-STING pathway and decrease oocyte quality in mouse - Si-Yao Cheng; Yi-Fan Yang; Ya-Long Wang; Zhao-Ping Yue; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2025)

Cable length prediction for towing models of reverse towing systems based on the cable deployment process - Hao Xu; Jun Wang; Ran Ling-ke; Jian Wang; Shunzhao Cheng; Xiaofeng Liang (Ocean Engineering, 2024)

Reconciled estimation of Antarctic ice sheet mass balance and contribution to global sea level change from 1996 to 2021 - Rongxing Li; Guojun Li; Gang Hai; Huan Xie; Yuan Cheng; Wei Chen; Xiangbin Cui; Minghu Ding; Chunchun Gao; Tong Hao; Changqing Ke; Chuanjin Li; et al. (Science China Earth Sciences, 2024)
The Antarctic Ice Sheet (AIS) has been losing ice mass and contributing to global sea level rise (GSLR). Given its mass that is enough to cause ∼58 m of GSLR, accurate estimation of mass balance trend is critical for AIS mass loss monitoring and sea level rise forecasting. Here, we present an improved approach to reconciled solutions of mass balance in AIS and its regions from multiple contributing solutions using the input-out, altimetric, and gravimetric methods. In comparison to previous methods, such as IMBIE 2018, this approach utilizes an adaptive data aggregation window to handle the heterogeneity of the contributing solutions, including the number of solutions, temporal distributions, uncertainties, and estimation techniques. We improved the regression-based method by using a two-step procedure that establishes ensembled solutions within each method (input-output, altimetry, or gravimetry) and then estimates the method-independent reconciled solutions. For the first time, 16 contributing solutions from 8 Chinese institutions are used to estimate the reconciled mass balance of AIS and its regions from 1996 to 2021. Our results show that AIS has lost a total ice mass of ∼3213±253 Gt during the period, an equivalent of ∼8.9±0.7 mm of GSLR. There is a sustained mass loss acceleration since 2006, from 88.1±3.6 Gt yr −1 during 1996–2005 to 130.7±8.4 Gt yr −1 during 2006–2013 and further to 157.0±9.0 Gt yr −1 during 2014–2021. The mass loss signal in the West Antarctica and Antarctic Peninsula is dominant and clearly presented in the reconciled estimation and contributing solutions, regardless of estimation methods used and fluctuation of surface mass balance. Uncertainty and challenges remain in mass balance estimation in East Antarctica. This reconciled estimation approach can be extended and applied for improved mass balance estimation in the Greenland Ice Sheet and mountain glacier regions.

Water flush boosts performance of elemental sulfur-based denitrification packed-bed systems: Optimization and mechanisms - Jia-Min Xu; Heng Dong; Hao-Ran Xu; Yi-Lu Sun; Yang Yu; Li-Ying Zhang; Gen-Ping Yi; Wen-Ke He; Chang-Min Wu; Ai-Jie Wang; Hao-Yi Cheng (Bioresource Technology, 2024)

The Alasu rock avalanche in the Tianshan Mountains, China: fragmentation, landforms, and kinematics - Qi-wen Lin; Yu-feng Wang; Qian-gong Cheng; Jing Huang; Hao-ran Tian; Guo-xiang Liu; Ke He (Landslides, 2024)

Estimating water surface evaporation losses under floating coverage: Modeling and Application - Ke-Wu Han; Ke-Bin Shi; Xin-Jun Yan; Fei Ling; Guo-Chen Hao; Qian-Ran Qin (Journal of Hydrology, 2023)

Alpha-ketoglutarate alleviates cadmium-induced inflammation by inhibiting the HIF1A-TNFAIP3 pathway in hepatocytes - Yinzhao Jia; Chuanzheng Yin; Wenbo Ke; Jing Liu; Bing Guo; Xiaofei Wang; Peng Zhao; Shaobo Hu; Chen Zhang; Xuan Li; Ran Liu; Xichuan Zheng; et al. (Science of The Total Environment, 2023)

Endophytic fungus Trichoderma atroviride D16 increases tanshinone accumulation in Salvia miltiorrhiza plantlets by enhancing abscisic acid and salicylic acid signaling - Xing-Guang Xie; Ke-Xin Sheng; Wei-Lan Lu; Hao-Ran Wang; Khalid Rahman; Kun-Miao Feng; Ting Han (Symbiosis, 2023)

Efficient oxidation of ammonium to nitrogen gas via accelerated ClO• generation at TiO2/Ru-IrO2 bifacial electrode in a UV-driven photoelectrochemical system - Yi Liu; Ran Mao; Jingwei Hao; Kaifeng Wang; Ke Hu; Yuexin Cui; Xu Zhao (Chemical Engineering Journal, 2023)

Dietary pattern interfered with the impacts of pesticide exposure by regulating the bioavailability and gut microbiota - Ai Song Chen; Dong Hui Liu; Hao Nan Hou; Jia Ning Yao; Shou Chun Xiao; Xiao Ran Ma; Pei Ze Li; Qian Cao; Xue Ke Liu; Zhi Qiang Zhou; Peng Wang (Science of The Total Environment, 2023)

Life cycle assessment of integrated bioelectrochemical-constructed wetland system: environmental sustainability and economic feasibility evaluation - Ying-Ke Fang; Hong-Cheng Wang; Pan-Hao Fang; Bin Liang; Kun Zheng; Qi Sun; Xi-Qi Li; Ran Zeng; Ai-Jie Wang (Resources, Conservation and Recycling, 2023)

Generation and identification of endothelial-specific Hrh2 knockout mice - Rui Meng; Wen-Ke Cai; Wen-Mang Xu; Qiang Feng; Ping Wang; Yan-hua Huang; Yu-Xin Fan; Tao Zhou; Qin Yang; Zhi-Ran Li; Gong-Hao He (Transgenic Research, 2021)